Genomic damage in Mugil curema (Actinopterygii: Mugilidae) reveals the effects of intense urbanization on estuaries in northeastern Brazil - Lima, Anderson R.B.; Torres, Rodrigo A.; Jacobina, Uedson P.; Pinheiro, Marcelo A.A. [UNESP]; Adam, Mônica L. (Elsevier, 2019)
The largest metropolitan centers in northeastern region of Brazil are all located near the coast, and industrial, tourist, and agro-industrial activities are the principal causes of water contamination due to discharges of untreated sewage. Adverse environmental conditions can often be detected by analyzing the genetic material of organisms exposed to pollutants, and furnish an overview of environmental quality. We evaluated possible damage to the DNA of one of the fish resources most widely consumed and commercialized by coastal communities in northeastern Brazil, Mugil curema (“tainha”). Erythrocytes from M. curema were analyzed by the presence of micronuclei and by comet assay (single cell gel electrophoresis, SCGE). Statistical comparisons to both tests revealed considerably greater genomic damage in polluted estuaries than in the control site (p < 0.05), suggesting strong genotoxic impacts on the specimens evaluated, principally among those taken near localities with dense demographic and industrial development.
Keywords: Comet assay; Environmental risk; Estuary systems; Micronucleus; Mullets; Water contamination